High-affinity binding of short peptides to major histocompatibility complex class II molecules by anchor combinations. - Hammer, J (1994)
We have previously identified four anchor positions in HLA-DRB1*0101-binding peptides, and three anchors involved in peptide binding to DRB1*0401 and DRB1*1101 molecules, by screening of an M13 peptide display library (approximately 20 million independent nonapeptides) for DR-binding activity. In this study, high stringency screening of the M13 library for DRB1*0401 binding has resulted in identification of three further anchor positions. Taken together, a peptide-binding motif has been obtained, in which six of seven positions show enrichment of certain residues. We have demonstrated an additive effect of anchors in two different ways: (i) the addition of more anchors is shown to compensate for progressive truncation of designer peptides; (ii) the incorporation of an increasing number of anchors into 6- or 7-residue-long designer peptides is shown to result in a gradual increase of binding affinity to the level of 13-residue-long high-affinity epitopes. The anchor at relative position 1 seems to be obligatory, in that its substitution abrogates binding completely, whereas the elimination of other anchors results only in partial loss of binding affinity. The spacing between anchors is critical, since their effect is lost by shifting them one position toward the N or C terminus. The information born out of this study has been successfully used to identify DR-binding sequences from natural proteins.